2021
DOI: 10.3390/biology10040334
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Boron Neutron Capture Therapy for Malignant Brain Tumor Patients in Compliance with Emergency and Compassionate Use: Evaluation of 34 Cases in Taiwan

Abstract: Although boron neutron capture therapy (BNCT) is a promising treatment option for malignant brain tumors, the optimal BNCT parameters for patients with immediately life-threatening, end-stage brain tumors remain unclear. We performed BNCT on 34 patients with life-threatening, end-stage brain tumors and analyzed the relationship between survival outcomes and BNCT parameters. Before BNCT, MRI and 18F-BPA-PET analyses were conducted to identify the tumor location/distribution and the tumor-to-normal tissue uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The early induction of bevacizumab treatment could suppress radiation toxicity after BNCT, as with other radiation therapies. Recently, a Taiwanese research group reported on BNCT of lower tumor dose (range, 8.51-25.09 Gy-equivalent) than other reports in treatment of recurrent MG with life-threatening, end-stage status [24]. Their median PFS and OS were 4.18 and 7.25 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The early induction of bevacizumab treatment could suppress radiation toxicity after BNCT, as with other radiation therapies. Recently, a Taiwanese research group reported on BNCT of lower tumor dose (range, 8.51-25.09 Gy-equivalent) than other reports in treatment of recurrent MG with life-threatening, end-stage status [24]. Their median PFS and OS were 4.18 and 7.25 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Taiwan, a total of 34 patients with malignant brain tumors in an immediately life-threatening condition who were treated by BNCT were investigated. The T/N ratio was a significant prognostic factor of cancer-specific survival, such as a 12-month survival rate with a T/N ratio < 3 (42%), 3-4 (22%), > 4 (100%), and the p value when the T/N ratio ≥ 4 and < 4 was 0.035, although the T/B ratio did not show a significant difference in overall, cancer-specific, and relapse-free survivals [27].…”
Section: Clinical Assessment Of 18 Fbpa Petmentioning
confidence: 93%
“…In this model, the maximum tumor RBE dose was determined to be 42.2 Gy-Eq and the mean tumor RBE dose was estimated to be 28.9 Gy-Eq [ 37 ]. Studies in malignant brain tumors and recurrent head and neck cancers treated with BNCT have demonstrated that doses of 18–25 Gy-E delivered to at least 80% of the tumor volume are associated with improved control rates [ 38 , 39 ]. More recently, a newer model of BNCT dose calculation known as the photon isoeffective model was developed and validated in a limited number of studies.…”
Section: Treatment Planning Considerations and Radiobiologic Aspects ...mentioning
confidence: 99%